Geotechnical properties of recycled construction and demolition materials for filling applications. (September 2020) - Ok, Bahadir; Sarici, Talha; Talaslioglu, Tugrul; Yildiz, Abdulazim
Graphical abstract: Highlights: Comprehensive laboratory tests were conducted on the C&D materials. The C&D materials were evaluated by comparing the virgin aggregate materials. C&D materials were compared with different recycled aggregates. The usability of C&D was evaluated by the various technical specifications. The design suggestions were presented. Abstract: Modern societies make a hard effort to improve the sustainability of resources due to enhanced environmental sensitivities in nowadays. This paper investigates the usability of recycled construction and demolition materials as an alternative to virgin aggregates in geotechnical applications such as the filling. The physical and geotechnical properties of recycled construction and demolition materials were determined by laboratory tests (i.e. sieve test, flatness test, Los Angeles abrasion test, water absorption test, pycnometer test, modified compaction test, California bearing ratio test, unconfined compressive strength test and resilient modulus test) and a comprehensive laboratory evaluation was carried out. Moreover, similar tests were conducted with a type of high-quality virgin aggregate material frequently used in fillings. The results of the tests conducted on construction and demolition materials were compared with results of the tests conducted on both virgin aggregate and different recycled aggregates which are accepted as an alternative to virgin aggregates used in the filling in the literature. Results of the tests conducted on construction and demolition materials were also evaluated according to the limit values in technical specifications of highway administrations of various countries. As a result of this study, it has been concluded that construction and demolition materials can be a good alternative to virgin aggregate used in the filling provided that it is taken measure against excessive water absorption value.